Learning (on) Local Terms: The Cantonese dictionaries of two Eighteenth-Century European Traders - Hellman, Lisa (chronotopos – A Journal of Translation History, 2022)
This article compares two manuscript dictionaries, that of John Bradby Blake and Johan Pontin. These dictionaries are Cantonese-English and Cantonese-Swedish respectively, and were both created as a result of a stay in the trading hub of Canton in the 1770s. Both dictionaries are shown to follow the word choice, word order and illustrations of Chinese textbooks for language learning, “zazi”. Such zazi were common tools for the linguistic standardisation and schooling reforms of the Qing Empire, but were also used in early European attempts to learn Chinese. Thereby, European efforts to learn Chinese is here shown to follow a Qing imperial pattern, and a non-European structure and logic. The bulk of the scholarship on early sinology in Europe focus on missionaries, and on activities in Beijing. That the two dictionaries studied here translate between European languages and Cantonese, rather than other Chinese dialects, and that they were compiled as part of a commercial, not a scholarly or religious contact, help show the importance also of Canton in the eighteenth century for European-Chinese translation history.